Stochastic heating of charged particles in absence of first order resonances - Antonov, A.N.; Buts, V.A.; Kornilov, E.A.; Svichensky, V.G.; Kuzmin, V.V.; Tolstoluzhsky, A.P. (Вопросы атомной науки и техники, 2015)
Dynamics of charged particles in external electromagnetic fields in the absence of resonances proportional to the first degree of intensity of an electromagnetic field is investigated. Two schemes are investigated. In the first existence of several regular electromagnetic waves is supposed. It is supposed that frequencies and wave vector of these waves are such that the phase velocity one of beating waves is close to thermal velocity of particles. It is essential that thus organized Cherenkov resonances are proportional to square of small parameter (a square of dimensionless intensity of the field). In the second scheme is supposed that the phase of the field of wave changes by jump under the random law. Parameters of the studied systems at which one or other scheme of transmission of energy the field to particles has advantage are found.